Analysis of Village-Owned Enterprises (BUMDes) Development Strategy in Increasing Village Own-source Revenue in Bantimurung, Maros Regency - Sitti Rahmawati Arfah; Nur Wahid; Nurbiah Tahir; Busri Busri (Universitas Muhammadiyah Gorontalo, 2021)
This article explains the development of Village Owned Enterprises (BUMDes) in increasing original villagel income during the pandemic covid-19, which hurts the socio economic antisocialeconomicall communities. The research location at BUMDes in Kecamatan Bantimurung, Kabupaten Maros, uses survey research method with descriptive analysis approach using SWOT analysis technique. The selection of respondents was carried out by purposive sampling of 36 respondents using the proportional random sampling technique. The research data consisted of primary and secondary data regarding the conditions, and internal and external factors of BUMDes in Bantimurung. Data was collected using interview techniques with research instruments in the form of questionnaires. Based on the results of the study, it shows that BUMDes in Bantimurung is not yet fully optimal but can contribute to village the own-source revenue with business units owned and the lack of facilities and supervision from the sub-district government, so that the BUMDes strategy that can be applied is the growth and build strategy, it can be recommended that the development of BUMDes need support from the government through regulations, capital assistance and accompaniment. In addition, by carrying out good strategic planning for the development of BUMDes, in-depth observations and mapping of the local economic potential of villages, choosing business development, and expanding the network of cooperation partners and optimizing the role of cooperation partners and the community to jointly encourage the development of BUMDes products, strengthen markets and training for BUMDes managers on an ongoing basis.